Studies on Morphological and Phylogenetic Relationship of Salak Pondoh Varieties (Salacca zalacca (Gaert.) Voss.) at Sleman Highlands. - HERWIN SUSKENDRIYATI; ARTA WIJAYATI; NUR HIDAYAH; DEWI CAHYUNINGDARI (Society for Indonesian Biodiversity, 2000)
The objectives of the study were to know the morphological variation of salak-plants (Salacca zalacca (Gaert.) Voss. and their relationship. The study was conducted in May to April 2000, at Turi and Pakem of Sleman district, Yogyakarta. Samples were randomly taken, 5 plants of each variety were studied their morphological characters such as stem, leaf, flower and fruit. The data collected were then analyzed descriptive comparatively and their relationships were then determined. The result of the study indicate that there were at least 8 varieties of salak at Sleman district, green-, black-, yellow-, manggala-, red-yellow-, golden-, red-, and red-black pondoh. Morphological differences among varieties were markedly different. The closest relationship was found between variety of red-black- and black pondoh, while the farthest relationship among the varieties was manggala pondoh.Â© 2000 Jurusan Biologi FMIPA UNS SurakartaKey words: Salacca zalacca (Gaert.) Voss.), morphology, variety.